FEATURES OF PATHOLOGY OF THE NOSE AND PARANASAL SINUSES IN PATIENTS WITH LOWER RESPIRATORY TRACT DISEASES - Bakieva, Sh.Kh.; Jumanov, D.A.; Jabborov, N.N. (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
Diseases of the upper and lower respiratory tract are closely related, since they are a reflection of the pathology of different parts of the same system. Due to the variety of pathogenetic mechanisms for the effective treatment of patients with respiratory tract diseases, it is optimal to use drugs that simultaneously act on different links of the pathogenesis of the disease, allowing the mucociliary clearance to be restored and the paranasal sinuses and bronchial tree to be freed from pathologically altered secretions. The best option for the treatment of the common cold is a drug that has both anti-inflammatory, antimicrobial, immunomodulating and secretolytic effects.